2015
DOI: 10.4252/wjsc.v7.i10.1215
|View full text |Cite
|
Sign up to set email alerts
|

Polymericvshydroxyapatite-based scaffolds on dental pulp stem cell proliferation and differentiation

Abstract: PLLA scaffold supports adhesion, proliferation and osteogenic differentiation of hDPSCs. Hence, it may be useful in combination with hDPSCs for cell-based reconstructive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The hMSCs seeded on nanocomposite PCL/HA scaffolds in 12-well plate and showed high proliferation in HA concentration-dependent manner as compared to Neat-PCL (Figure 4). Additionally, previous studies have demonstrated that PCL/HA-based scaffolds showed high proliferation and osteogenic differentiation in human dental pulp stem cells (hDPSCs) and mouse adipose-derived stem cells (ADSCs) (33, 34). Interestingly, magnetic bioinspired hybrid nanocomposite collagen-hydroxyapatite scaffolds enhanced cellular proliferation and restored bone generation (35, 36).…”
Section: Resultsmentioning
confidence: 99%
“…The hMSCs seeded on nanocomposite PCL/HA scaffolds in 12-well plate and showed high proliferation in HA concentration-dependent manner as compared to Neat-PCL (Figure 4). Additionally, previous studies have demonstrated that PCL/HA-based scaffolds showed high proliferation and osteogenic differentiation in human dental pulp stem cells (hDPSCs) and mouse adipose-derived stem cells (ADSCs) (33, 34). Interestingly, magnetic bioinspired hybrid nanocomposite collagen-hydroxyapatite scaffolds enhanced cellular proliferation and restored bone generation (35, 36).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that PLLA scaffolds supported adhesion, proliferation, and osteogenic differentiation of hDPSCS compared to other scaffolds. For the current study the expression patterns of both markers at 14 and 21 days showed that 14-day cultivation periods is adequate for hSHEDs with/without PLA scaffolds to differentiate into osteoblasts (30). …”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve successful regeneration, the scaffolds, cells, and bioactive signaling molecules are required to induce stem cell differentiation into the dental tissue type (11). An ideal scaffold should be able to interact with cells, offer a platform for cell adhesion and proliferation, and enhance the regeneration of tissue (12). Early studies on dental pulp tissue engineering with tooth slices or segments have used polylactic or polyglycolic acid (PLGA) as scaffold materials.…”
Section: Types Of Scaffolding For Tissue Engineering In Dental Pulp Rmentioning
confidence: 99%